Reliability of maximum isometric force-time parameters during a leg press test in pubertal basketball players - Ioakimidis, P.; Gerodimos, V.; Kellis, E.; Kellis, S. (Pediatric Exercise Science, 2002)
Fifteen young basketball players (aged 14.4 ± 0.5 yrs) underwent two identical testing sessions spaced one week apart, to determine the reliability of maximum isometric force and force-time parameters during a maximal bilateral isometric leg press effort. The maximal isometric force (MIF), the ratio of maximal force to time (TMIF) to attain maximal force (ARMIF), starting strength (F50), and on a relative scale the time taken to increase the force from 10% to 30%, 60%, and 90% of maximal force were calculated. High intraclass correlation coefficients (ICC) were found for MIF (0.96), ARMIF (0.85), and F50 (0.90). On the relative scale, the ICCs for the times to produce 30%, 60%, and 90% of maximum force were 0.94, 0.95, 0.95, respectively. The present results indicate that maximum isometric force and the force-time parameters during a bilateral leg press can be measured reliably in pubertal basketball players.